Experimental study of the effect of water-cement ratio on compressive strength, abrasion resistance, porosity and permeability of Nano silica concrete (Fracture and Structural Integrity, 2018)
The effect of water-cement ratio on abrasion resistance, porosity and hydraulic conductivity coefficient of Nano silica concrete have been studied in this research (paper). The compressive strength of concrete in a particular temperature is related to two factors: water-cement ratio and density. Decreasing the water-cement ratio from 0.46 to 0.30 improves the abrasion resistance of Nano silica concrete by 42%, the hydraulic conductivity coefficient of concrete decreases from 28.5⤬10-15 to 1.7⤬10-15 m/s and the porosity of concrete decreases to 13.1%. The abrasion depth increases gradually by increasing the water-cement ratio from 0.30 to 0.46.
Keywords: Abrasion resistance; Compressive strength; Concrete; Permeability; Water-Cement Ratio